2020
DOI: 10.1016/j.bandl.2020.104840
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive neurostimulation of left ventral motor cortex enhances sensorimotor adaptation in speech production

Abstract: Sensorimotor adaptation-enduring changes to motor commands due to sensory feedback-allows speakers to match their articulations to intended speech acoustics. How the brain integrates auditory feedback to modify speech motor commands and what limits the degree of these modifications remain unknown. Here, we investigated the role of speech motor cortex in modifying stored speech motor plans. In a within-subjects design, participants underwent separate sessions of sham and anodal transcranial direct current stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…We suggest, therefore, that the articulatory representation in left M1 is involved in generating a form of adaptation that aims to move speech production closer to a learnt pattern of speech production used to produce another vowel. It is worth noting, however, that compensatory changes in F2 did not occur in Scott et al. (2020) , under either sham or anodal motor stimulation.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…We suggest, therefore, that the articulatory representation in left M1 is involved in generating a form of adaptation that aims to move speech production closer to a learnt pattern of speech production used to produce another vowel. It is worth noting, however, that compensatory changes in F2 did not occur in Scott et al. (2020) , under either sham or anodal motor stimulation.…”
Section: Discussionmentioning
confidence: 82%
“…F1 compensatory changes in the same speech adaptation task were enhanced by anodal tDCS (which typically increases excitability) of left ventral motor cortex and right cerebellum relative to sham stimulation ( Lametti et al., 2018a ). A more recent study similarly found that high-definition anodal tDCS of the ventral motor cortex also enhanced compensation in F1 in response to F1 feedback perturbation ( Scott et al., 2020 ). Taken together, the results from these three studies confirm an important role for left speech motor cortex in speech adaptation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the domain of speech production, tDCS was most often applied over the frontal regions of the left hemisphere, which improved speech motor learning in healthy individuals 43 , 44 and facilitated speech production in neurodegenerative apraxia of speech 45 . Two studies also demonstrated beneficial effects of anodal tDCS placed more posteriorly on motor speech learning and rehabilitation.…”
mentioning
confidence: 99%
“…Prediction errors typically occur due to structural changes in speech articulators (e.g., rapid developmental changes during childhood or structural changes during the aging process) or sensory feedback (e.g., hearing impairment) (Daliri et al, 2013; Perkell, 2012; Perkell et al, 1992; Pittman et al, 2018; Vorperian et al, 2005, 2009). One could generate prediction errors in the laboratory setting by experimentally manipulating somatosensory feedback (Daliri et al, 2013; Lametti et al, 2012; Tremblay et al, 2003) or auditory feedback (Abur et al, 2018; Ballard et al, 2018; Daliri et al, 2017; Daliri & Max, 2018; Houde & Jordan, 1998; Kim et al, 2020; Kothare et al, 2020; Scott et al, 2020; Stepp et al, 2017). Due to practical reasons and the importance of auditory feedback for speech production, many studies have used auditory perturbations to induce auditory prediction errors during speaking (for a review, see Fuchs et al, 2019).…”
mentioning
confidence: 99%